Transformational Leadership in the Perspective of Islamic Education: A Comparative Analysis of Al-Ghazali's Thought and Modern Leadership Theory - Sita Arum Damayanti; Faqih Abdul Aziz; Iffatut Tazkiyyah (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2025)
Leadership in Islamic educational institutions continuously faces a critical dichotomy between the relentless demands of modern, secular transformational management and the imperative to preserve classical religious values. This study aims to comparatively analyze the epistemological and ontological foundations of Al-Ghazali’s leadership thought and modern transformational leadership theory to construct an integrative synthesis. Employing a qualitative library research method with a historical-philosophical and comparative approach, this study extracts conceptual data from Al-Ghazali’s classical texts alongside foundational theories developed by Burns and Bass. The results reveal a profound paradigmatic contrast: transformational leadership operates on a positivistic, anthropocentric epistemology focused exclusively on observable organizational behaviors (the Four I's), whereas Al-Ghazali’s framework relies on a theocentric (Tawhid) foundation emphasizing internal moral character. To resolve this dichotomy, this study constructs the